2012
DOI: 10.5402/2012/824671
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome after Resection Rectopexy for Internal Rectal Intussusception

Abstract: Background and Aims. The optimal treatment of patients with internal rectal intussusception (IRI) is unresolved. The aim was to study the short- and long-term outcome of resection rectopexy in these patients. Methods. An observational and mainly prospective study of 48 patients (44 women) with IRI who had ligament-preserving suture rectopexy by laparoscopic (n = 25) or open (n = 23) technique. Outcome measures were morbidity, scores for constipation and anal incontinence, patients' report, and health-related q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Ventral mesh rectopexy, as described by D'Hoore et al . , was reported in ten studies and resection rectopexy in four . Abdominal rectopexy was performed laparoscopically in all the studies and in four open rectopexy was also used (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Ventral mesh rectopexy, as described by D'Hoore et al . , was reported in ten studies and resection rectopexy in four . Abdominal rectopexy was performed laparoscopically in all the studies and in four open rectopexy was also used (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…All patients had internal rectal prolapse (IRP) diagnosed clinically, by defaecography and/or by examination under anaesthesia. Eight studies , including 971 patients, reported the presence of a concomitant anterior rectocele in 671 (69.1%) patients. Ten studies, which included 1158 patients, classified rectoanal intussusception according to the Oxford grading system as Grade I–II in 50 (4.4%) patients and Grade III–V in 1108 (95.6%).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations